HUBUNGAN TEKNIK MENYUSUI DENGAN TERJADINYA LECET PUTING SUSU PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS PEMBANTU DESA TAMANSARI KECAMATAN MUMBULSARI KABUPATEN JEMBER - Rizka Yuliatul H (Jurnal Kesehatan dr. Soebandi, 2015)
Breastfeeding is the process of giving food to a baby by using breast milk directly from the breast. According to WHO (2009) there were 35.6% of mothers failing to breastfeed their babies and 20% of them were mothers in developing countries, while based on data from the Basic Health Research (Riskesdas) in 2010 it was explained that 67.5% of mothers who failed to breastfeed exclusive to the baby. The purpose of this research is to know the relationship between breastfeeding techniques and the occurrence of nipple blisters on postpartum mothers in the Pustu Working Area of ​​Tamansari Village, Mumbulsari District, Jember Regency. This type of research is analytic. The population in this study was 57 people. The sample size used by 50 people with a sampling technique is purposive sampling. Data were analyzed using a computer with Statistical Product and Service Solution (SPSS) 16.0 for Windows. The results obtained by the majority of puerperal breastfeeding techniques are wrong 27 (54%), experienced 25 blisters (50%). Based on data analysis, the calculated value of x2 (13,607)> x2 table (3,481), with a significance value of 0,000 <0.05, so that in this study the hypothesis is accepted. The conclusion of this study is that there is a relationship between breastfeeding techniques and the occurrence of nipple blisters on postpartum mothers in Pustu Tamansari Village, Mumbulsari Subdistrict, Jember Regency in 2014 with the strength of the relationship category is quite significant or moderate. Health workers always provide counseling about breastfeeding techniques to reduce the risk of blisters.